THE USE OF CLUSTERING TECHNIQUE IN TEACHING LEARNING PROCESS OF WRITING DESCRIPTIVE TEXT BY THE EIGHTH GRADE STUDENTS OF SMP PARULIAN 2 MEDAN - Stevan Evander Juan Fagio; Willem Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2020)
This study aims to find out how is the process of teaching learning descriptive text by using clustering technique for the eighth grade students of SMP Parulian 2 Medan. This study was conducted by using qualitative research. The data of this study were collected by using observation, interview, and survey. the result of observation, interiew, and survey prove that the use of clustering technique in teaching learning process of writing descriptive text was good percentage (83%) of the students were interested and followed every step in clustering technique, In the first step of clustering technique, the teacher introduced clustering technique and all students paid attention. All students  got 3 score (100%), it means 30 students participated well in the process of clustering technique. In the second step, the teacher showed the example of clustering technique and only some students who asked. All the students got 1 score (33,3%) it means only 10 students asked in the process of clustering technique, In the third step, the teacher led the students to generate idea in form of clustering technique. All students focused to generate the idea based on the teacher’s directions in form of clustering technique. All students got 3 score (100%), all the 30 students participated well in the process of clustering technique, in the forth step the teacher asked the students to write the first draft based on the design of clustering technique. All students wrote their own descriptive text using clustering technique based on the teacher direction and the example that had been given by the teacher. All the students got 3 score (100%). From this result, the researcher concludes that both teacher and students participated well in the process of teaching learning descriptive text by using clustering technique for the eighth grade students of SMP Parulian 2 Medan.